ABU HANIFAH DAN METODOLOGI ISTIHSAN DALAM ISTINBATH HUKUM - Hafilah Rahimah (Makkah: Journal Of Islamic Studies, 2025)
This research aims to know the figure of mujtahid Abu Hanifah and his method in istinbath a law, istihsan is a characteristic attributed to this madzhab. Istihsan has a significant role in contributing as a method of determining Islamic law in religious, social, economic and health fields. Although it is still debated to be used as a proof, it is still used in several aspects of resolving a law by other madhhabs. This research uses qualitative methods, the types of data used are primary and secondary data. And the method of collecting data for this research is by literature study. The results of this study are to open insights to readers about the figure of the great mujtahid Abu Hanifah and his istinbath method in formulating the law, explaining the concept of istihsan Hanafi madzhab and differences in fuqaha opinion to be used as an argument, and the implementation of istihsan law that occurs in everyday life in society.